Angolan coffee revival - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Angola s civil war saw its famous coffee sector fall from a production level of 204,000 tonnes in 1970 to 5,200 tonnes in 1999, barely enough for local consumption; it even had to import its beloved beans. Now the International Coffee Organisation...